(untitled) (Conferences, 2026)
. This article examines issues of healthcare in the Uzbek SSR during the Soviet era, specifically: healthcare services for the population, diseases that emerged in the region, measures to eradicate them, existing problems, the creation of a healthcare system, the construction and maintenance of hospitals, and the provision of the country with doctors.